Walls and remembrance,Talking home - M-Afrika, Andile Ernest (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
This is a story of a quest that begins on a wall of history at a cemetery where Steve Biko was buried. The main character is the writer, who is partly the author, partly a fictionalised everyman. He is on a journey of self-discovery, while at the same time questioning contemporary South Africa.
Keywords: Creative writing (Higher education); South African fiction (English) -- 21st century; English language -- Writing